PERLINDUNGAN HUKUM TERHADAP PENUMPANG TANPA TIKET (ILLEGAL) DALAM PENGANGKUTAN DARAT DI INDONESIA - Wahyu Nugraha, I G A; A. Martana, Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014)
This paper is titled “Legal Protection for The Passengers Without Tickets (Illegal) on Land Transporter in Indonesia”. This paper uses analytical method and statute approach. Transporter as an agreement is always preceded by an agreement between the parties of carrier and the passenger or shipper. The duty of carrier and the passengers or stuffs to the destination have been agreed safely. It’s quite different while the passenger don’t have own the ticket so that the transporter could not obligate to fulfill the rights of passenger.
Keywords: Legal Protection, Passenger Without Ticket, Land Transporter